Kepercayaan Diri Relawan di Ruang Digital: Studi Fenomenologi dalam Perspektif Psikologi Kewarganegaraan - Ludovikus Bomans Wadu; Andri Fransiskus Gultom; Priskardus Hermanto Candra (University of Muhammadiyah Malang, 2026)
This study explores how digital psychological experiences influence the self-confidence of volunteers within the context of contemporary civic engagement. Employing a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design, the research delves into the subjective experiences of three founders of an Indonesian volunteer-based Non-Governmental Organization (NGO). Data were collected through in-depth semi-structured interviews, supplemented by documentation analysis and non-participant observation. The findings reveal that volunteers' self-confidence is constructed through a dynamic and dialectical process shaped by their interactions in digital spaces. Social media platforms function as ambivalent psychological arenas, simultaneously providing validation and posing threats. In response, volunteers develop a form of dynamic self-confidence, anchored in two pillars: evidence-based efficacy (rooted in tangible impact) and value-based resilience (rooted in intrinsic motivation and preparedness). To sustain this confidence, they employ dual resilience strategies: collective emotion regulation within their team and personal digital literacy practices, such as selective detachment. The study concludes that sustaining civic engagement in the digital era requires not only instrumental skills but also the psychosocial capacity to navigate the complex psychological landscape of online spaces.